Implikasi Missio Dei dalam Interaksi Sosial: Menemukan Dimensi Transformasi Pariwisata di Objek Wisata Air Soda Parbubu Tarutung - Eliyunus Gulo; Esra Siahaan; Dian Lumbantobing; Josep Harianja; Josua Simatupang; Aldo Tambunan (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2026)
This study aims to overhaul the conventional understanding of tourism through a missiological lens, by positioning social interactions at the Parbubu Tarutung Soda Water Tourism Object as the locus of Missio Dei (God's Mission) manifestation. Amidst the tendency of modern humans to be trapped in egocentrism, alienation, and minimal openness due to secular routines, God is present with a mission to transform human relations. Using a qualitative descriptive-theological method, this study analyzes three axes of social interaction (inter-tourists, tourists-managers, and tourists-local communities). The results of field research indicate that although the pattern of interaction between visitors is still minimalist and egocentric-group due to a purely physical recreation orientation, there is a strong spiritual modality in the service aspect (hospitality) of the managers that reflects the restoration of the image of God (Imago Dei). The absence of social conflict and the presence of sincere hospitality are identified not merely as business strategies, but as real implications of the work of the Holy Spirit who precedes the church (prevenient grace) in destroying human egoism. This study concludes that tourism can be an eschatological means by which social interactions are transformed into encounters that bring about God's Shalom, meaning that tourism can be a way to bring about God's peace through authentic encounters between tourists, rather than simply ordinary tourist transactions. The author recommends the reconstruction of public spaces in this destination as inclusive communal spaces that facilitate reconciliation and social transformation.